3D printed magnetic polymer composite hydrogels for hyperthermia and magnetic field driven structural manipulation. (August 2022) - Ganguly, Sayan; Margel, Shlomo
Abstract: Magnetic hydrogels and soft composites have fueled the development of next generation biomimetic soft robotics due to their precise control and non-cytotoxic nature. Bare magnetic nanoparticles are difficult to regulate via remote controlling whereas, when these nanoparticles are arrested inside polymeric matrices, the whole system become an artificial soft mussel like integrated system. Concurrently, these polymeric magnetic soft materials are also prone to response of external magnetic field (static or oscillatory). Additive manufacturing via spatial assembly of polymeric precursors followed by actuation like behavior is quite a new manufacturing technique to fabricate magnetic soft materials. In this review, we focused on the magnetic nanoparticles and their entrapment into polymeric matrices and assessing their applicability in clinical (hyperthermia) as well as shape morphing behaviours. Both the behaviors are also amassed together to form dual responsive soft microbots. The techniques and their applications are elaborated in this review. Graphical abstract: Image, graphical abstract